Study of the prevalence of dental fluorosis in school children from Belém, Pará State, Brazil - Gonçalves, Aline Carvalho (2020)
Dental fluorosis is an injury caused by excessive and prolonged intake of fluoride compounds during tooth formation, being preventable if monitored by the oral health surveillance system. This is a cross-sectional study that was carried out in 2011, in order to identify the prevalence of dental fluorosis in 12-year-old schoolchildren in the City of Belém, Pará State, Brazil. It was used the Dean's Index and the systematic random sampling with 124 children according to data collected from the Municipal Department of Education. It was found a 40% prevalence of dental fluorosis among children examined: 27% (n = 33) in a very low level of fluorosis, 7% (n = 9) light level, 5% (n = 6) questionable and 1% (n = 2) moderate. There was no record of severe fluorosis. The prevalence of fluorosis was high compared to other Brazilian regions, although it has been shown in a lightly way in the studied population, there was no significant epidemiological problem related to the disease severity. However, it is emphasized the importance of a rigorous monitoring of the fluoride levels used to prevent dental caries in water consumed.